Biological Applications and Toxicity Minimization of Semiconductor Quantum Dots. Issue 2 (February 2020) - Filali, Samira; Pirot, Fabrice; Miossec, Pierre
Abstract : The extraordinary potential of semiconductor quantum dots (QDs) has resulted in their widespread application in various fields, from engineering technology and the development of laboratory techniques to biomedical imaging and therapeutic strategies. However, the toxicity of QDs remains a concern and has limited their applications in human health. Better understanding of the behavior of QDs as it relates to their composition will enable the exploration of their limitations and development of a strategy to control their toxicity for potential therapeutic applications. Here, we describe approaches to minimize their toxicities according to the specific cell type, organ, or animal species, summarizing recent promising research at the cellular, organ, and whole-organism level. Highlights: QDs of varying composition may be designed, enabling the modulation of their effects accordingly. Approximately half of the studies carried out over the past 5 years focused on the same type of QDs, mainly from the same supplier. Overall, QD accumulation occurs in the liver, kidney, spleen, and lungs. Further studies are needed to clarify the effects according to a concentration range. Data on QD pharmacokinetics are beginning to emerge; however, more in-depth and better structured studies are needed to support these results. Promising applications are being evaluated, particularly in the treatment of degenerative and/or infectious diseases; in particular, interesting results for the treatment and diagnosis of multiresistant bacterial diseases have been obtained. The first tests in non-human primates are encouraging because they show a lack of significant toxicity.